Optimal seismic retrofitted RC column distribution for an existing school building. (1st August 2018) - Seo, Hyunsu; Kim, Jinsup; Kwon, Minho
Highlights: Optimization study on minimum number and location of seismic retrofitted columns. Empirical results obtained through time-history analysis on a three-story school. Retrofitting 60.2% of the columns could withstand ground acceleration of 0.2 g. Abstract: Seismic retrofit technology has been significantly developed to reduce building damage during earthquakes. However, earthquakes are unpredictable natural disasters that should be dealt with flexibly. Hence, the seismic retrofitting method should be independently studied. In this study, the minimum number and the location of seismic retrofitted reinforced concrete columns required for school buildings in service are derived through an optimization technique. A time-history dynamic analysis of the frame structure comprising columns and beams is conducted using a three-dimensional finite element model to obtain empirical results. The study subject is a school building, which is a three-story RC structure with non-seismic details consisting of 62 RC columns on each floor (i.e., a total of 186 columns). The optimization analysis showed that retrofitting only 60.2% of the columns could withstand a peak ground acceleration of 0.2 g applied at the shear critical regions at both column ends.